Psychosocial factors associated with overdose subsequent to Illicit Drug use: a systematic review and narrative synthesis - Christopher J. Byrne; Fabio Sani; Donna Thain; Emma H. Fletcher; Amy Malaguti (BMC, 2024)
Abstract Background and aims Psychological and social status, and environmental context, may mediate the likelihood of experiencing overdose subsequent to illicit drug use. The aim of this systematic review was to identify and synthesise psychosocial factors associated with overdose among people who use drugs. Methods This review was registered on Prospero (CRD42021242495). Systematic record searches were undertaken in databases of peer-reviewed literature (Medline, Embase, PsycINFO, and Cinahl) and grey literature sources (Google Scholar) for work published up to and including 14 February 2023. Reference lists of selected full-text papers were searched for additional records. Studies were eligible if they included people who use drugs with a focus on relationships between psychosocial factors and overdose subsequent to illicit drug use. Results were tabulated and narratively synthesised. Results Twenty-six studies were included in the review, with 150,625 participants: of those 3,383-4072 (3%) experienced overdose. Twenty-one (81%) studies were conducted in North America and 23 (89%) reported polydrug use. Psychosocial factors associated with risk of overdose (n = 103) were identified and thematically organised into ten groups. These were: income; housing instability; incarceration; traumatic experiences; overdose risk perception and past experience; healthcare experiences; perception of own drug use and injecting skills; injecting setting; conditions with physical environment; and social network traits. Conclusions Global rates of overdose continue to increase, and many guidelines recommend psychosocial interventions for dependent drug use. The factors identified here provide useful targets for practitioners to focus on at the individual level, but many identified will require wider policy changes to affect positive change. Future research should seek to develop and trial interventions targeting factors identified, whilst advocacy for key policy reforms to reduce harm must continue.